Evaluation of Routine Coagulation Parameter in Suspected Acute Myocardial Infarction Patients Attending Emergency Department of Tertiary Care Hospital - Mishra, Mritunjay Kumar; Ramavataram, DVSS; Shah, Tejas (Journal of clinical and diagnostic research, 2021)
Introduction: Heart attack in medical terminology is generally called as Acute Myocardial Infarction (AMI). When blood flow is abruptly cut-off to the heart muscle, it damages the myocardial tissue. This could be the consequence of blocked coronary arteries. The plaque formed due to the deposition of cholesterol and other fatty material over a period of time is the leading cause of this blockage. Aim: To assess the level of Prothrombin Time (PT) and activated Partial Thromboplastin Time (aPTT) in cardiac and non-cardiac chest pain and their association to Body Mass Index (BMI). Materials and Methods: The present study was an observational case-control type of study which included 100 subjects of age group 30-65 years from March 2019 to April 2020. Out of them 50 were non-cardiac chest pain individuals which were control and 50 Cardiac chest pain arrived within 6-8 hours of chest pain who suspected to be Myocardial Infarction (MI) from Emergency Department, Dhiraj General Hospital, Gujarat, India. BMI was calculated by height and weight. PT and aPTT analysis was carried out using STAGO-S.A.S. coagulation analyser. Results: There were increased levels of PT and aPTT (statistically significant) in AMI cases compared to corresponding age and sex matched controls (p<0.0001). Pearson correlation analysis in AMI patients, a slightly positive correlation between BMI and aPTT was observed (r=0.19, p<0.001) and also between PT and aPTT (r=0.66, p<0.001). Conclusion: There was a slightly positive correlation found between BMI and aPTT which indicated that the weight and height of the patients do not affect the plasma PT and aPTT levels on anticoagulant therapy.